Reassessment of post-construction residual settlement of a bridge approach embankment using Bayesian back analysis - Shan Huang; Jinsong Huang; Merrick Jones; AHM Kamruzzaman; Richard Kelly; Stanley Yuen (Transportation Geotechnics, 2025)

Predicting settlement of embankments built on PVD-improved soil using Bayesian back analysis and elasto-viscoplastic modelling - Shan Huang; Jinsong Huang; Richard Kelly; Merrick Jones; A.H.M. Kamruzzaman (Computers and Geotechnics, 2023)

Substratum selection in coral reef sponges and their interactions with other benthic organisms - Saúl González-Murcia; Merrick Ekins; Tom C. L. Bridge; Christopher N. Battershill; Geoffrey P. Jones (Coral Reefs, 2023)
Substratum preferences and contact interactions among sessile organisms can be a major determinant of biotic gradients in the structure of benthic communities on coral reefs. Sponges are a substantial component of these communities, but their substratum requirements and interactions with other benthic taxa are poorly understood. Here, we quantified sponge substratum preferences and interactions from 838 randomly selected photo-quadrats across different depths (5, 10 and 15 m), exposure (sheltered and exposed), and substratum topography (horizontal, inclined and vertical surfaces) on coastal coral reefs in Kimbe Bay. A high proportion (55%) of sponge colonies were associated with dead coral, unconsolidated coral rubble (7%) and calcium carbonate rock (CaCO 3 rock) (7%), even though they represented only 10%, 4% and 1% of the available substratum, respectively. Sponges interacted most frequently with algae (~ 34%), corals (~ 30%) and crustose coralline algae (CCA ~ 19%) that represented ~ 46%, ~ 18% and ~ 14% of the substratum cover, respectively. The microhabitat preferences of sponges and frequency of interactions with other taxa were mostly consistent across various exposure, depth and substratum topography conditions. Most interactions appeared to be “stand-offs” (71%) which are interactions with no clear winner or loser. However, when overgrowth occurred, sponges were usually winners, overgrowing corals (92%), CCA (81%) and macroalgae (65%). Three sponge species Dysidea sp1, Lamellodysidea cf. chlorea and Lamellodysidea chlorea accounted for 51% to 96% of the overgrowth of sponges over algae, corals and CCA, but there was no one species found to always win or lose. Our results suggest that sponges avoid other biological substrata by preferentially settling on dead coral, coral rubble and CaCO 3 rock, but when they do come into contact with algae and corals, they frequently overgrow their spacial competitors.